Parental educational aspiration and gender inequality of rural children in Bangladesh: The role of parental attitudes of traditional gender role, gender biased capability, and gender - Sarker, Shahidul Islam; Karim, A.H.M Zehadul; Abu Suffiun, Samrat Mohammad (Bridgewater State University, 2017)
This study investigates how gender inequality in higher education is produced by the attitudes of parents in rural Bangladesh. To this end we examine (i) parental traditional gender role attitude, (ii) parental attitude toward girls’ capability and (iii) parental gender biased investment attitude as three types of parental attitudes based on the responses of 435 rural parents in which 52.05% were parents of boys and 56.25% of girls. We conduct logistic regression analysis to determine whether the observe variables (these three types of attitudes) significantly predict the odds of parental aspiration for higher education and whether the effects of these predictors significantly differ in parental aspiration outcome according to the gender of children. Results in the nested model (model 3) show that after controlling the parental background variables (income and education), these three types of parental attitudes have individual significant impact on parental educational aspiration in which, if these attitudes increase, it significantly decreases the odds of having parental aspiration of higher education for their children. Furthermore, in the separate modes for boys and girls we observe that if these three types of attitudes increase, the likelihood of having parental aspiration of higher education significantly increase only for the case of boys but significantly decrease for the case of girls.